2016
DOI: 10.15585/mmwr.su6501a3
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion and Diabetes Prevention in American Indian and Alaska Native Communities — Traditional Foods Project, 2008–2014

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 32 publications
1
49
0
Order By: Relevance
“…Prevention should be critically informed by the social contexts that shape the health of Indigenous peoples, as well as resourced to ensure effectiveness and sustainability. For example, the United States-based Traditional Foods Project aimed to increase access to traditional foods, physical activity and social support (88). Indigenous communities across the country applied their traditional ecological knowledge, specific to the history and culture of their tribe, to protect their communities' land, languages, culture, memory and traditional food practices.…”
Section: Primary Preventionmentioning
confidence: 99%
“…Prevention should be critically informed by the social contexts that shape the health of Indigenous peoples, as well as resourced to ensure effectiveness and sustainability. For example, the United States-based Traditional Foods Project aimed to increase access to traditional foods, physical activity and social support (88). Indigenous communities across the country applied their traditional ecological knowledge, specific to the history and culture of their tribe, to protect their communities' land, languages, culture, memory and traditional food practices.…”
Section: Primary Preventionmentioning
confidence: 99%
“…The many heterogenous American Indian/Native Alaskan (AI/NA) and immigrant populations provide powerful examples to consider in dialogues around access to cultural and religious foods. Reinforcing traditional foods and cultural practices is a promising approach to address the disproportionately high rates of diabetes experienced by many AI/NA groups (Satterfield et al 2016). Some research suggests that the nutrition transition that AI/NA populations experienced over the course of history is partially responsible (Story et al 1998;Welty, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of Native American women, Goins et al (290) found that A1C and poor diabetes control correlated with psychological trauma and low social support. In the Traditional Foods Project (2008-2014), local HCP and community members were engaged to prevent T2D through sustainable, evaluable, and ecological approaches (291). A network of other programs to benefit Native Americans that emphasize physical activity as part of T2D prevention include those funded by the Special Diabetes Program for Indians, the Together Raising Awareness for Indian Life (TRAIL), the IHS National Congress of American Indians and Division of Diabetes Treatment and Prevention, Boys and Girls Clubs, Nike, FirstPic, Inc, and the Office of Women's Health (280).…”
Section: Diabetes Carementioning
confidence: 99%